The tasks of the system ensuring the protection of entrepreneurship in Ukraine - Беззубов, Дмитро Олександрович; Бухер, Марія Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article presents the tasks of ensuring the protection of entrepreneurship in Ukraine in modern conditions. Identifies and analyzes the objectives and functions of the system of economic security of entrepreneurship. The analysis of constituent entities of the system of economic security levels of management and functional competencies.